The efficacy and safety of temperature controlled dual-mode radiofrequency in women with vaginal laxity - Lixia FU; Senyang Long; Qin LI; Hainan XU; Ling Guo; Huarong Wang; Zhongyan Zheng; Jing Zhang (BMC Women's Health, 2023)
Abstract Objective Vaginal laxity could negatively influence women’s sexual function. This study aimed to explore the efficacy and safety of temperature controlled dual-mode (monopolar and bipolar) radiofrequency (RF) in women with vaginal laxity. Methods A total of 102 patients with vaginal laxity were treated with temperature-controlled RF. The present study implemented Vaginal Laxity Questionnaire (VLQ), Female Sexual Function Index (FSFI) questionnaire and Sexual Satisfaction Questionnaire (SSQ) on all patients at baseline and after treatment. Pelvic Organ Prolapse Quantification System (POP-Q) system was applied to physical examination, and vaginal manometer to examine the strength of voluntary contractions of the pelvic floor muscles. Results The VLQ score was gradually increased after RF treatment at 1, 3, 6 and 12 months, accompanying by the significant improvement in total FSFI scores and the six domains (sexual desire, sexual arousal, lubrication, orgasm, satisfaction, pain). The increased sexual satisfaction based on the SSQ score was found after temperature-controlled RF. The result of POP-Q stage showed significant difference in women after treatment, with the women having Stage I of 45.10% at baseline, 36.27% at 1 month, 28.43% at 3 months, 19.61% at 6 months and 10.78% at 12 months. The mean pressure and mean duration of pelvic contractions were increased gradually at the 1-, 3-, 6- and 12- month follow-up. Conclusion Temperature controlled dual-mode (monopolar and bipolar) radiofrequency may be associated with improvement of vaginal laxity, and contribute to enhancement to female sexual function and pelvic floor muscles.